Quantifying the durability of transition metal nitrides in thermoplasmonics at the single-nanoparticle level - Kenji Setoura (AIP Publishing LLC, 2021)
Heat generation of plasmonic nanoparticles under photo-illumination is of great use as nanoscale sources for chemical reactions and materials processing; the term thermoplasmonics has been infiltrating in the research fields related to nanotechnology, which represents photothermal effects in plasmonics. In recent years, transition metal nitrides have attracted much attention as thermoplasmonic materials because of their excellent thermal properties compared with those of noble metals. The transition metal nitrides such as titanium nitride (TiN) and zirconium nitride (ZrN) exhibit optical properties similar to gold, and their melting points are very high; for instance, the melting points are 1337 and 3253 K for gold and ZrN, respectively. However, nanometer-sized materials are known to melt at lower temperatures compared with bulk melting points (e.g., around 580 K for gold nanoparticles); this phenomenon is called surface melting, premelting, surface diffusion, or photothermal reshaping. In the present work, we evaluated threshold temperatures of the laser-induced photothermal reshaping of ZrN nanocubes by the scattering micro-spectroscopy at the single-nanoparticle level. As a result, the threshold temperatures of the photothermal reshaping ranged from 1400 to 2100 K; these temperatures are much higher than that of the gold nanoparticles. This work proved that the transition metal nitrides are suitable for thermoplasmonics at higher temperatures compared to the noble metals.